THE COPPER-PORPHYRY AND GOLD-SULFIDE MINERALIZATIONS OF THE DASTAKERT AND AREVIS ORE FIELDS (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
In the article copper-porphyry ore fields uncovered by varying degrees of erosion are described. On eroded Dastakert ore field copper-porphyry mineralization is opened, but on Arevis less eroded part, accompanying gold-sulphide mineralization is preserved. Within the first ore field the two different age copper-porphyry mineralizations are manifested.
Keywords: ore field; erosion; copper-porphyry mineralization; gold-sulfidemineralization; geological structure